Penerapan Model Problem Based Learning (PBL) Berbantuan Media Puzzle untuk Meningkatkan Pemahaman Konsep Komponen Peta pada Mata Pelajaran IPAS Peserta Didik Kelas IV Sekolah Dasar - Wahyuni, Eka; Adi Winanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students’ conceptual understanding of map components in the Natural and Social Sciences (IPAS) subject through the implementation of the Problem Based Learning (PBL) model assisted by puzzle media among fourth-grade elementary school students. This study employed Classroom Action Research (CAR), which was conducted in two cycles consisting of planning, action implementation, observation, and reflection stages. The subjects of this study were 20 fourth-grade students at an elementary school in Pagubugan Kulon Village, Binangun District, Cilacap Regency. Data were collected through observation, interviews, tests, and documentation. The data were analyzed using descriptive quantitative and descriptive qualitative techniques. The results showed an improvement in students’ conceptual understanding at each stage of the action. In the pre-action stage, the students’ average score was 68.5, with a learning mastery percentage of 40%. After the implementation of Cycle I, the average score increased to 78.0, with a learning mastery percentage of 70%. In Cycle II, the average score further increased to 87.5, with a learning mastery percentage of 90%. In addition, students’ learning activities also improved, as indicated by increased active participation in discussions, confidence in expressing opinions, group cooperation, and enthusiasm in participating in the learning process. Therefore, the implementation of the Problem Based Learning model assisted by puzzle media can improve fourth-grade elementary school students’ conceptual understanding of map components in the IPAS subject.